EKONOMI KREATIF SEBAGAI PENDORONG PEMULIHAN EKONOMI PADA MASA NEW NORMAL DI KABUPATEN BANYUMAS - Nugrah Leksono Putri Handayani; Poppy Fitrijanti Soeparan (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
Deteriorating economic conditions due to the Covid-19 pandemic are now starting to rise, the government has reopened economic activity during the New Normal period. In economic activities, business actors carry out various innovations and creativity to form a creative economy from various aspects. This study aims to find out how the creative economy can encourage economic recovery during the new normal period in Banyumas Regency. This research uses descriptive analysis method with qualitative data. The results of this study indicate that the potential of the creative economy in Banyumas Regency is quite good, the superior sub-sectors are performing arts, culinary and applications. There is good potential, support for facilities, the community, MSMEs and local government so that the economy in Banyumas Regency begins to improve. It can be seen from the economic growth of Banyumas Regency which was recorded at 4.0% in 2021.